TEACHERS, CURRICULUM AND PROBLEMS: A CRITICAL REFLECTION ON EDUCATION - Loso Judijanto; Agustin Nurya Savitri; Darry Christine Silowaty Purba (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This article examines the relationship between teachers, curriculum and various problems in the education system through critical reflection. Teachers play a central role in curriculum implementation and its influence on the quality of student learning. Nonetheless, they are often faced with various challenges, including lack of welfare, limited professional training and high workloads, which impact on their ability to teach effectively. In addition, rigid curricula that are sometimes irrelevant to 21st century needs often hinder the development of students' cognitive and creative capacities. These problems highlight the need for a more flexible and adaptive curriculum revision and the contribution of all parties in creating a better education system. Collaboration between the government, education managers, teachers and the community is needed to produce an education that not only focuses on academic knowledge, but also on developing important life skills for students.